2017
DOI: 10.1002/jsfa.8349
|View full text |Cite
|
Sign up to set email alerts
|

Influence on wine biogenic amine composition of modifications to soil N availability and grapevine N by cover crops

Abstract: Wine biogenic amine concentration can be affected by the grapevine nitrogen status, provoked by changes in the soil NO -N availability with both cover crop treatments. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Histidine, tyrosine, tryptophan, lysine, phenylalanine and arginine are also known to be precursors of biogenic amines (i.e. histamine, tyramine, tryptamine, cadaverine, phenylethylamine, agmatine and putrescine), which are undesired in wine production due to their negative health effects and unpleasant odours 37,38 . Notably, the U‐ACP treatment produced grapes with a lower concentration in most of these amino acids (apart from tryptophan) compared to the U6 treatment (Figs 2 and 3 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Histidine, tyrosine, tryptophan, lysine, phenylalanine and arginine are also known to be precursors of biogenic amines (i.e. histamine, tyramine, tryptamine, cadaverine, phenylethylamine, agmatine and putrescine), which are undesired in wine production due to their negative health effects and unpleasant odours 37,38 . Notably, the U‐ACP treatment produced grapes with a lower concentration in most of these amino acids (apart from tryptophan) compared to the U6 treatment (Figs 2 and 3 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…According to Gutierrez-Gamboa et al [ 39 ], the most abundant amino acids observed in red wines are usually Pro, Arg, Glu, Ala and Asp, while the least abundant amino acids generally found in these wines are Cys, Tyr, Ile, Trp and Leu. Wines with higher amounts of residual nitrogen together with other factors, have greater risks of microbiological instability and the production of ethyl carbamate and biogenic amines [ 52 , 53 , 54 , 55 , 56 ]. As it has been mentioned before, yeast assimilable nitrogen (YAN) is a combination of free amino acids and ammonium (NH 4 ), both the main nitrogen sources since they contribute to the sensory properties, microbiological stability and flavor of wines [ 57 , 58 ] and also proline.…”
Section: Resultsmentioning
confidence: 99%
“…These effects depend on climate, parent soil matrix, plant species, and management practices (use of temporary or permanent cover crops). It was found that cover cropping influences wine quality by reducing acidity and ammonia, due to an increase in anthocyanins . Some studies indicated that this practice could induce nutrient and water competition between cover crop and vines .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that cover cropping influences wine quality by reducing acidity and ammonia, due to an increase in anthocyanins. 7,8 Some studies indicated that this practice could induce nutrient and water competition between cover crop and vines. 5,9 It was also hypothesized, but less studied that cover cropping could reduce trace metals in the soil and their uptake by the main crops via different mechanisms (i) immobilization of trace metals in the roots of the cover crop; 10 (ii) competition in uptake between crops; 11 and (iii) phytostabilization by the release of metal complexing exudates.…”
Section: Introductionmentioning
confidence: 99%